Ieslodzīto un no ieslodzījuma atbrīvoto personu aktuālākās problēmas - Rimkeviča, Inga (Latvijas Universitāte, 2010)
Title of this paper is relevant difficulties, which prisoners and jail released people face with.. Aim of this work is to analyse problems of former prisoners, research professional competence of social worker in work with prisoners and former prisoners. Author of this work sets four tasks: 1. To analyse problems of prisoners and former prisoners; 2. To describe professional competence of social worker in context of social work; 3. To describe social work in probation with former prisoners; 4. To analyse expert opinions about professional competence in work with former prisoners. Work contains three chapters. In the first author researches problems of prisoners and former prisoners. In the second chapter author describes and experience which should be continuously improved. In the third, author researches possibilities of probation of former prisoners. During this work author concludes that problems of prisoners and former prisoners are specific and different; also competence of social workers should be adequate for solving various social problems. Social worker competence is bases on wide knowledge, skills and experience which should be continuously improved. In every institution there is some specific in work with former prisoners, competent social worker in work with former prisoners follows his work description.
Relevant difficulties of prisoners and jail released people
Keywords: Juridiskā zinātne